Pengaruh Karakteristik Pekerjaan Terhadap Kepuasan Kerja Karyawan Di Perumda Tirta Medal Sumedang - aldirafi gani (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2023)
Job characteristics and employee job satisfaction are important things that need to be considered so that work can be in accordance with company standards and individual standards. Enriched job characteristics can bring up positive feelings that lead to employee job satisfaction and vice versa can be bad for employees. The purpose of this study was to determine the effect of job characteristics on employee job satisfaction. The type of research used is descriptive verification with a quantitative approach. The population in this study were 502 employees of Perumda Tirta Medal Sumedang. The sample in this study amounted to 85 people based on the calculation of the Slovin formula. The sampling technique used in this study was proportional random sampling by taking samples from each section in Perumda Tirta Medal Sumedang. The data collection method used is by distributing questionnaires, interviews, observation and documentation. The data analysis used is descriptive analysis and statistical analysis with the t test as a hypothesis test. The conclusion from the results of the research that has been done shows that job characteristics influence employee job satisfaction.